Low-Cost Solar Energy Harvesting: A Study on Dye-Sensitized Solar Cells Using Inthanin Leaf Extract as a Natural Photosensitizer: Dye-Sensitized Solar Cells Using Inthanin Leaf Extract as a Natural Photosensitizer - Maria Onyemowo; Yuwalee Unpaprom; Rameshprabu Ramaraj (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
The world is actively pursuing renewable energy resources to combat environmental pollution and greenhouse gas emissions caused by the burning of fossil fuels. Solar energy is the most abundant, continuously available form of renewable energy, and dye-sensitized solar cells (DSSCs) are being explored as an alternative to traditional silicon-based solar cells due to their low cost of materials, ease of production, and efficiency. The photoanode is a crucial component in DSSCs, and the main challenges faced by these solar cells are charge recombination and low light harvesting ability. This study aims to investigate the efficacy of natural dyes as the sensitizer for the fabrication of DSSCs. Natural pigments were extracted from Inthanin leaves using the solvent extraction technique. The concentration and composition of the pigment were analyzed through pigment analysis utilizing UV a spectrophotometer. Inthanin has a higher chlorophyll a to b ratio. A higher chlorophyll a to b ratio has been shown to be associated with improved light harvesting and electron transport efficiency. This is because chlorophyll a is more efficient at transferring electrons to the electron transport chain than chlorophyll b. The higher chlorophyll a to b ratio could lead to improved electron transfer to the photoanode. The photoelectric parameters of the DSSC were evaluated using I-V characterization. DSSCs coated with Inthanin dye extract produced a short circuit current density (Jsc) of 0.02 mA/cm2, open circuit voltage (Voc) of 0.07 V, fill factor (FF) of 33% and an efficiency (????) of 0.1%.